Quality Improvement In Education Through The Forum Of Silaturrahim And Communication Of Muhammadiyah Middle School And MTS Principals (FOSKAM) - Rozaq Akbar; Muhammad Fazlurrahman Hadi; Rahmat Arafah Hari Cahyadi (Jurnal Ilmu Sosial Mamangan, 2024)
This research investigates the role of the Forum of Silaturrahim and Communication of Muhammadiyah Middle School and MTs Principals (FOSKAM) in efforts to improve the quality of education at Muhammadiyah Middle School 4 Porong Sidoarjo. Through a qualitative approach with a case study design, data were collected through observation, interviews, and document analysis. The results of the research indicate that FOSKAM serves as a collaborative platform facilitating the exchange of information, sharing experiences, and collectively devising strategies among the principals of Muhammadiyah middle schools. These findings underscore the importance of forums for fostering a supportive learning community aimed at enhancing the quality of education. The implications of these findings provide valuable insights for the development of managerial practices among school principals and educational management in middle schools.